Communication Skills in Medicine: A Review - Hussain, Md Margub (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Effective communication is fundamental for efficient healthcare delivery. It enhances and ensures standards of patient care, patient safety and satisfaction. It fosters a positive and collaborative environment enabling and safeguarding standards of patient care and also teaching and training in medicine. In practice different methods of communication are used in complex combinations for meaningful exchange of information. Each component skill carries its significance for transfer of intended information, ideas and spirits. Dearth in any of these skills may alter the theme of the massage. Hence a high level of competence in each of them is essential for complete and undistorted communication. Behavioral communication has significant impact for health care personals in all capacities. This paper is a brief review of different skills considered essential for physicians in their professional practice. J Bangladesh Coll Phys Surg 2026; 44: 47-59